Surface runoff estimate in urbanized area from the Rangel Stream basin at São Sebastião do Paraíso/MG - Almeida, Amanda Francieli de; Okawa, Cristhiane Michiko Passos (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2019)
Urban growth generates impacts over land usage and may alter the hydrological systems of a microbasin. The unregularized occupation impermeabilizes the soil and increase the volume and velocity of superficial runoff. Thus, inundation, flood and overflow occur in urban areas. In this context, this work’s objective was to quantify the impact of soil impermeabilization over the surface runoff coefficient in the microbasin of the Liso stream at São Sebastião do Paraíso county, Minas Gerais. Google Earth satellite images were used for the identification and determination of occupied urban areas, and ArcGis 10.4 software was utilized for letter elaboration, which determined the permeable areas. It was taken as hypothesis that the surface runoff coefficient is equal to one in impermeabilized areas. In addition, green areas and unoccupied allotments were considered as permeable areas. In order to determine the impermeabilized area, the permeable area was subtracted from the total area. The surface runoff coefficient was estimated as the relation between the impermeabilized area and the total urbanized area. The results have demonstrated that the urbanized area located in the microbasin grew 44,47% in ten years. Therefore, the estimate of surface runoff coefficient utilized in this paper can be a good alternative for city halls to analyze the urban growth and aid in the circumscription of residential areas or green areas, since it is a simple method which requires data easily generated through maps.